Optimizing the Service Provision time in the Emergency Department Using Mathematical Modeling and Simulation (Case Study: Imam Reza Hospital) - Mahdi Yousefi Nejad Atari; Ensiyeh Neyshabouri Jami; Akbar Sattari (مدیریت مهندسی و رایانش نرم)
Patient waiting time, the costs, and nurses’ job satisfaction level are important criteria in providing services in hospital.  One of the main causes of long patient waiting times is the lack of sufficient expert staff in the hospital. Increased costs and low job satisfaction of nursing staff in hospitals are the result of applying traditional and nonscientific methods in assigning nurses to shifts. The emergency department is one of the special units in the hospital, in which studying the patient flow is highly important. In this study, the current status of Imam Reza Hospital emergency department in Tabriz, Iran is simulated using ARENA 14 software, in order to assess the costs and size of the waiting line. Then, the current status of this department is compared with three scenarios with different number of nurses. In order to evaluate the costs and nurse job satisfaction in each scenario, a nonlinear integer programming mathematical model is proposed. In this model, nurses are properly assigned to shifts and weekdays in order to minimize the costs and to increase nurse job satisfaction. Finally, analyzing both nonlinear programming and simulation model, the results show that the number of nurses in this department is not sufficient and that six nurses should be added to the staff.